Estudo dos mecanismos envolvidos na resolução da resposta inflamatória alérgica em camundongos induzida por espécies reativas de oxigênio (ROS) - Alesandra Côrte Reis (2015)
Introduction: Eosinophils are effector cells that have an important role in the pathogenesis of allergic disease. Defective removal of these cells likely leads to chronic inflammatory diseases such as asthma. Thus, there is great interest in understanding the mechanisms responsible for the elimination of eosinophils from inflammatory sites. Previous studies have demonstrated a role for certain mediators and molecular pathways responsible for the survival and death of leukocytes at sites of inflammation. Reactive oxygen species have been described as proinflammatory mediators but their role in the resolution phase of inflammation is poorly understood. The aim of this study was to investigate the mechanisms whereby hydrogen peroxide resolves the allergic inflammatory responses. Material and methods: An eosinophilic cell line (Eol-1) was treated with hydrogen peroxide and apoptosis was measured. Allergic inflammation was induced in ovalbumin sensitized and challenged mouse and reactive oxygen species were administered at the peak of inflammatory cell infiltrate. Inflammatory cell numbers, cytokine and chemokine levels, mucus production, inflammatory cell apoptosis and peribronchiolar matrix deposition was quantified in the lungs. Resistance and elastance were measured at baseline and after aerosolized methacholine. The expression of caspase-3 and signal transduction pathways in leukocytes were measured of immunofluorescence and confocal analysis. Phosphatidylserine expression was measured after hyrdrogen peroxide treatment in leukocytes by flow cytometry. Results: Hydrogen peroxide accelerates resolution of airway inflammation by induction of caspasedependent apoptosis of eosinophils and inhibit survival from of pathways in eosinophils especifically. Moreover, H2O2 decrease remodeling, mucus deposition, inflammatory cytokine production and airway hyperreactivity. Conclusion: These data presented indicate a pro-resolving effect of hydrogen peroxide in allergic inflammation by inducing apoptosis of eosinophils, and inhibiting cell survival pathways. These results, could have fundamental implications for the basic concept of resolution of inflammation and may have therapeutic implications.